Modelling of the predicted thermal comfort of the metro passengers under different crowd densities. (23rd May 2019) - He, Zhiying; Chen, Chunjun; Yang, Gang; Yan, Lei
The aim of this study is to find out the nature of the metro passenger's thermal comfort under different crowd densities and different ambient environment factors. Taking the human factors, garment factors and ambient environmental factors into consideration, a sub-model human thermal perception was investigated based on the Fanger's heat balance equation. Also, a steady thermal sub-model of the B-type metro vehicle was built based on the heat conservation among the passengers, the outside-vehicle environment and the air of human-vehicle system. Then, the human thermal perception and its alternation were quantified by applying the PMV index. Simulation results show that the passenger's thermal perception cannot only variates with the airflow velocity, the relative humidity and the volume of the new air, but also with the crowd density.